2008
DOI: 10.1002/cmr.a.20118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular oxygen as a paramagnetic NMR probe of protein solvent exposure and topology

Abstract: This review focuses on the applications of dissolved oxygen in NMR studies of protein topology. A brief discussion is given to explain the origin of O 2 -induced paramagnetic shifts and relaxation rate enhancements, which are seen for a variety of nuclei of biological interest-in particular 13 C, 19 F, and 1 H. We also give examples of applications of paramagnetic effects from dissolved O 2 , which include studies of solvent exposure, hydrophobicity, transient contacts or local clustering in intrinsically diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Penetration of dissolved oxygen (O 2 ) into proteins was originally investigated by quenching of fluorescence 16 17 . The paramagnetic effects of O 2 , such as paramagnetic shifts and paramagnetic relaxation enhancements (PREs), have been used to study protein solvent exposure and topology by NMR spectroscopy 18 19 20 21 . Although many crystal structures of heme-proteins with O 2 ligands and their migration processes inside the proteins have been investigated by X-ray crystallography 22 23 and molecular dynamics (MD) simulation 24 25 , to the best of our knowledge, association of O 2 with internal cavities of proteins in solution has been investigated by NMR spectroscopy only for ribonuclease A 12 26 , deoxymyoglobin 13 , and the B domain of protein A 20 .…”
mentioning
confidence: 99%
“…Penetration of dissolved oxygen (O 2 ) into proteins was originally investigated by quenching of fluorescence 16 17 . The paramagnetic effects of O 2 , such as paramagnetic shifts and paramagnetic relaxation enhancements (PREs), have been used to study protein solvent exposure and topology by NMR spectroscopy 18 19 20 21 . Although many crystal structures of heme-proteins with O 2 ligands and their migration processes inside the proteins have been investigated by X-ray crystallography 22 23 and molecular dynamics (MD) simulation 24 25 , to the best of our knowledge, association of O 2 with internal cavities of proteins in solution has been investigated by NMR spectroscopy only for ribonuclease A 12 26 , deoxymyoglobin 13 , and the B domain of protein A 20 .…”
mentioning
confidence: 99%
“…If the pseudo-contact shift dominated, the magnitudes of chemical shift changes for the bound nuclei would be to a similar degree in ppm. However, similarity of O 2 -induced chemical shifts among 1 H, 13 C, and 15 N nuclei were not observed. More details surrounding this observation were previously discussed.…”
Section: Dissociation Constants Of Omentioning
confidence: 82%
“…NMR provides a high‐resolution approach to investigate the structure and dynamics of proteins in solution. Several studies have shown that NMR spectroscopy in combination with dioxygen (O 2 ) gas‐pressure is a powerful tool for investigating the location of internal protein cavities and pockets in solution and their accessibility to ligands, owing to the paramagnetic properties of O 2 . In previous studies, methods to analyze O 2 ‐binding sites in proteins in solution were reported, using the O 2 ‐induced enhancement of backbone amide proton spin‐lattice relaxation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen presents distinct advantages as a sPRE probe owing to its small size and ubiquitous nature. However, one needs to bear in mind that significant PREs on 1 H and 19 F can only be observed at pressures of 20–60 bar 11. Additionally, analysis can be obscured by the inherent electrostatic bias that predominates the interaction between oxygen and the solute.…”
Section: Spre Probesmentioning
confidence: 99%